The Mushroom at the End of the World. On the Possibility of Life in Capitalist Ruins. Anna L. Tsing - Alvarado Portillo, Patricia (Alteridades, 2018)
Reseña del libro de Anna L. Tsing, "The mushroom at the end of the world. On the possibility of life in capitalist ruins", Princeton University Press, Princeton, 2015, 331 pp.